Legal Aspects Of Liquidation Of The Bank Against The Customer - Muda Sipayung, Iskandar (International Asia Of Law and Money Laundering, 2023)
The purpose of writing this article is to be able to determine the regulation of legal aspects of liquidation that have an impact on customers when a bank is liquidated. The method used to study this article is the normative legal research method. In huku research methodsm normative approach is using legislation- invitation and conceptual approach as a way to solve the problem based on legal materials obtained and analyzed by the description technique qualitative . After reviewing the results obtained that arrangements related to bank liquidation in the banking system in Indonesia have actually been arranged. This can be seen in the Banking Act, the UU LPS, Government Regulation No. 25 of 1999 and other provisions. Basically, the decree contains the same thing, namely that liquidation is the end of bank failure. In the event that the bank is liquidated, the bank must return the deposits held by customers. If the assets owned by the bank are insufficient, the commissioners, directors and shareholders can be held accountable to meet the obligations of the bank.